Misi Amanat Agung: Sebuah Kajian Komparatif Perspektif Calvinis dan Arminian - Hendra Suherman; Jimmy Lizardo; Sugihyono Sugihyono (Sekolah Tinggi Teologi Baptis, Jakarta, 2023)
This article aims to describe the Great Commission as Jesus' command to make disciples of all nations from the perspective of missiology, Calvinism, and Arminianism. This study uses a qualitative approach, with the literature study method, using book sources and research articles as a reference for studying the meaning of the great commission in its true sense. The result of this research is the need to communicate the two different views above with the concept of